PENGARUH PERTUMBUHAN EKONOMI DAN INVESTASI TERHADAP KETIMPANGAN PENDAPATAN DI KABUPETEN/KOTA PROVINSI NUSA TENGGARA BARAT - Mohammad Royan; Wahyu Hidayat Riyanto; Ida Nuraini (Jurnal Ilmu Ekonomi JIE, 2019)
The distinction of interzonal potential will cause several problems such as uneven economic growth, the area-centered spreading investment, and income inequality. This research aims to analyze the effect of economic growth and investment on the inter-regional income inequality in West Nusa Tenggara from 2012 to 2017. This research uses secondary data obtained from BPS-Statistics Indonesia (Badan Pusat Statistik), and the Indonesian Investment Coordinating Board (Badan Koordinasi Penanaman Modal – BPKM). Williamson Index is used to representing income inequality, and the method analysis is the panel data analyzing with a Fixed Effect Model (FEM). The effect between a dependent variable and independent variable will be shown that economic growth has a positive and significant influence towards the income inequality, and investment has a positive and not significant influence towards the income inequality.